Peran Orang Tua di Pedesaan Dalam Melestarikan Bahasa Aceh Sebagai Warisan Budaya di Kalangan Generasi Z (Studi di Desa Linggong Sagoe, Kec. Simpang Tiga, Kab. Pidie) - Fifi Alayda; Syukri Syamaun; Taufik Taufik (Journal of Innovative and Creativity, 2026)
The Acehnese language is an important part of Acehnese society, as it is through this language that values, customs, and traditions are passed down from generation to generation. However, many young people, especially Generation Z, are now rarely using the Acehnese language in their daily lives. They more often use Indonesian, even mixing it with slang or language from social media. As a result, the Acehnese language is becoming less used, especially at home and in the surrounding environment. This study was conducted in Linggong Sagoe village, Simpang Tiga District, Pidie Regency, to examine the role of parents in preserving and maintaining the Acehnese language among rural youth. The study employed a qualitative method, involving direct interviews with a number of parents, generasi Z individuals, and village officials. The results indicate that parents play a significant role in instilling the habit of speaking Acehnese at home. Therefore, parents who consistently speak Acehnese with their children ensure that their children become accustomed to and do not forget their regional language. However, there are also those who prefer to use Indonesian because they feel that their children understand it more easily, or because of the influence of schools and social media, which mostly use Indonesian. From these results, it can be concluded that the preservation of the Acehnese language needs to be done collectively. It is not enough for only parents to play a role; support from schools and the community is also needed.